The Effect of Radiocontrast Exposure on Kidney Function of Cardiac Catheterization Patients - Heba Abuhelala; Intisar Abukel (Khalij-Libya Journal of Dental and Medical Research, 2026)
One of the important organs in the body is the kidneys, and its primary function is to remove excess fluids and salts from the body and regulate blood pressure and many other balance factors. One medically important diagnostic and therapeutic procedure is cardiac catheterization, which can lead to acute kidney injury (AKI). Risk factors that predict the development of acute renal failure after cardiac catheterization include exposure to contrast materials. It is one of the essential elements of angiography. Providing contrast dye has disadvantages, especially in those who already have renal impairment, as they may develop contrast-induced nephropathy. This study aimed to investigate cardiac catheterization patients who were injected with contrast agent and compare the results of kidney function before and after cardiac catheterization for 3 days, and also compare the volume of contrast agent that was injected and the dose of radiation to which the patient is exposed, and compare kidney function (creatinine and urea) before and after cardiac catheterization. This cross-sectional descriptive study was conducted in private clinics, and 119 cases who underwent cardiac catheterization were collected; their ages ranged from 28 to 90 years. COBAS INTEGRA 400 PLUS was used to analyze the samples. The contrast agents used in angiography are Ultravist 370, Omnipaque 350, and Visipaque 320. The dose varies according to the patient's age, weight, and health condition. The results of the urea and creatinine test before and after cardiac catheterization showed that only urea levels changed after cardiac catheterization, and the results were statistically significant, P < 0.05. While the levels of urea and creatinine in people with chronic kidney disease did not differ, the results did not differ as urea decreased after cardiac catheterization. While comparing males and females, the results were found to be statistically significant, P < 0.05 for males. In light of the results of the study and its discussion, it was concluded that the contrast materials used in cardiac catheterization affect the kidney functions of patients. Kidney function levels may be affected by some factors, including contrast volume and intravenous fluids after cardiac catheterization. Medical history and duration of illness.